2009
DOI: 10.1007/s00210-009-0448-2
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive activity and toxicology of the lectin from Canavalia boliviana seeds in mice

Abstract: The aim of the present study was to evaluate the potential antinociceptive and toxicity of Canavalia boliviana lectin (CboL) using different methods in mice. The role of carbohydrate-binding sites was also investigated. CboL given to mice daily for 14 days at doses of 5 mg/kg did not cause any observable toxicity. CboL (1, 5, and 10 mg/kg) administered to mice intravenously inhibited abdominal constrictions induced by acetic acid and the two phases of the formalin test. In the hot plate and tail immersion test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
5
19
0
Order By: Relevance
“…The involvement of the opioid system in lectin activity has already been demonstrated, as in the naloxone‐induced reversion of the antinociceptive effect of lectins from Bryothamnion seaforthii , Bryothamnion triquetrum , and C. boliviana [4,7] and the opioid regulation of hyperinsulinemia by the lectin from Canavalia ensiformis (which is 99% homologous with ConBr) [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of the opioid system in lectin activity has already been demonstrated, as in the naloxone‐induced reversion of the antinociceptive effect of lectins from Bryothamnion seaforthii , Bryothamnion triquetrum , and C. boliviana [4,7] and the opioid regulation of hyperinsulinemia by the lectin from Canavalia ensiformis (which is 99% homologous with ConBr) [41].…”
Section: Discussionmentioning
confidence: 99%
“…First described for algal lectins [4], antinociceptive effects were subsequently observed in mice injected intravenously with leguminous lectins. Thus, lectins extracted from Lonchocarpus sericeus and Canavalia grandiflora inhibited mechanical hypernociception [5,6], while the lectin of Canavalia boliviana inhibited central and peripheral nociception via the opioid system [7]. In another recent study from our group, Diocleinae lectins ( Canavalia maritima , C. grandiflora , Dioclea guianensis , Dioclea violacea, and Cratylia floribunda ) produced antinociceptive effects inhibiting acetic acid–induced writhing in mice when administered orally [8].…”
Section: Introductionmentioning
confidence: 99%
“…The referred experimental model has been widely applied to verify analgesic activity promoted by lectins present in vegetal species (Holanda et al, 2009) and algae , as observed in a lectin-like protein purified from Clitoria fairchildiana seeds, in which dose-dependent antinociceptive activity was also reported (Leite et al, 2012). The lectinic site seems to be involved significantly on the lectin-promoted antinociceptive activity, as reported in the analgesic agglutinins isolated from C. boliviana seeds and the red algae Pterocladiella capilacea, in which previous association of these lectins with their specific carbohydrates (glycose and mucin) blocked the protein from exert its function against the painful stimulus, resulting in no contortion inhibition (Figueiredo et al, 2009;Silva et al, 2010).…”
Section: Acetic Acid-induced Abdominal Contortion Modelmentioning
confidence: 88%
“…The effect of lectins on painful stimuli has presented wide variation of stimulated receptors. The algae lectins appear to act mainly on the peripheral nervous system (Bitencourt et al, 2008;Vanderlei et al, 2010), and the legume lectins appear to act at the Central Nervous System (de Freitas Pires et al, 2013;Figueiredo et al, 2009), although it is not a universal claim. Figure 6.…”
Section: Formalin Methodsmentioning
confidence: 99%
“…A considerable number of marine invertebrate lectins have already been purified and characterized, and considerable attention is focused on its biological recognition role [8][9][10][11][12]. The Table I summarizes the origin, specificity, and biological activity from some lectins [5,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Then, they come as ancestral molecules that show a high degree of conservation during the evolution to superior vertebrates [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%